KONSEPSI ARAH KIBLAT TANAH HARAM PERSPEKTIF HADIS - Indayati, Wiwik (ELFALAKY: Jurnal Ilmu Falak, 2021)
Prayer is mandatory worship for Muslims all over the world. One of the legal requirements of prayer is facing towards the Qibla. If a Muslim prayer is facing a direction other than Qibla, its prayer is not valid. The Islamic Mecca is the Kaaba, between east amd west. This paper will be explained to prayer to face the Kaaba. This obligation applies to those who can see the Kaaba in person (‘ainul Ka’bah) and who are in the region far from the Kaaba and cannot see it firsthand, it is imperative to face the Kaaba (jihatul Ka’bah). The scholars, however, agreed that those who could not see the Kaaba would have permission to know the direction of the Kaaba (jihatul Ka’bah), which would require them to look at the building of the Kaaba (‘ainul Ka’bah). ‘Ainul Ka’bah is the building of the Kaaba in Mecca. Whereas Jihatul Ka’bah was the direction to the Kaaba.